The complete chloroplast genome of Quercus robur 'Fastigiata'. Issue 1 (2nd January 2020) - Feng, Lijuan; Yang, Xuemei; Jiao, Qiqing; Wang, Chuanzeng; Yin, Yanlei
Abstract: The Quercus robur 'Fastigiata' is an important ornamental plant, in which the complete chloroplast genome (accession no. MN562095) was identified and sequenced. The genome size is 161, 172 bp, with a large single-copy (LSC, 90, 505 bp) region, a small single-copy (SSC, 18, 997 bp) region, and two inverted repeat regions (IRs, 25, 835 bp each). A total of 134 genes are successfully annotated, including 89 protein-coding genes, 37 tRNA genes, and 8 rRNA genes. The phylogenetic relationships inferred that Q. robur 'Fastigiata' is closely related to Quercus mongolica, Quercus wutaishanica, and Quercus dentata .